Design and Build a Customer Segmentation Website at the Hijabiken Online Store - Oktania Purwaningrum; Amalia Anjani Arifiyanti; Dhian Satria Yudha Kartika (Procedia of Engineering and Life Science, 2022)
Data can be processed to produce useful information for an organization/company. Example of transaction data that is processed to segment customers. Customer segmentation needs to be done so that sellers can find out market conditions and can be taken into consideration in developing marketing strategies. Customer segmentation can also make sellers know their customers well. Of course, customer segmentation needs to be done at the Hijabiken Online Store, this store sells Muslim products such as hijabs. Seeing the current conditions in the store, data storage is still manual which can be prone to damage and loss. Therefore, in this study, we will build a website that can store and process transaction data. Website design using DFD, CDM, PDM, and mockups. Segmentation is carried out using data mining science in the clustering process. Clustering is done with the K-Means algorithm and LRFM model. The results of testing every function of the website can be run properly.